50.7k views
2 votes
FIND WHAT DID I DO WRONG
(-2)(-3)(-4)=(-6)(-4)=24

User Banging
by
6.2k points

1 Answer

7 votes

Answer:

It should look like this (-2)(-3)(4) = (-6)(-4) = 24

Explanation:

You have to change the first -4 into a positive 4.

LOOK WHT YOU DID

(-2)(-3) = 6(-4) = -24

THE CORRECT WAY

(-2)(-3) = 6(4) = 24

So the equation should look like this (-2)(-3)(4) = (-6)(-4) = 24

See you only did one thing that's okay everyone makes mistakes!

Hope this helps ya! Keep smiling!

User Jocel
by
6.2k points